A case of Alport syndrome - Kaluvai, Sai Indraneel; K. V., Rajalakshmi; Y., Dayanandan (International Journal of Advances in Medicine, 2023)
Alport syndrome is an inherited disease characterized by progressive renal failure, hearing loss and ocular abnormalities. It usually manifests as progressive form of glomerular disease that is often associated with sensorineural hearing loss and ocular abnormalities. The defects are caused by mutations in the genes that code for type IV collagen’s alpha chains, which are the most important structural elements of basement membranes, including those in the kidney, cochlea, and eye. We present a 37-year-old female known case of chronic kidney disease on medical management came with complaints of shortness of breath and loss of appetite. Her 2 children are also affected. Her renal biopsy showed glomerulosclerosis, splitting, lamination of basement membrane. Pure tone audiometry revealed bilateral sensorineural hearing loss. Slit lamp examination showed bilateral lenticonus and distant direct ophthalmoscopy revealed oil droplet sign which confirms lenticonus with dot and fleck retinopathy. Hence diagnosed as a previously undetected case of Alport syndrome.